DIAGNOSTICO DEL SECTOR DEL BIODIESEL PARA SU POSIBLE FORTALECIMIENTO DE SUS CAPACIDADES EXPORTADORAS DESDE EL AÑO 2016 AL 2022 - Rodriguez B, Lina Y, Jennifer Rodriguez R (Universidad Antonio Nariño, 2024)
This research monograph is focused on a study of the biodiesel sector, which is a vegetable-based fuel that contributes to sustainable development and replaces fossil fuels. The main objective of the research was to conduct a diagnosis of the biodiesel sector in Colombia for the possible strengthening of export capacities, analyzing its regulatory framework, production process, costs, export destinations, and market opportunities. For the development of the research, a descriptive and exploratory scope was used, due to the limited research available in the sector. A methodology with a qualitative and quantitative approach is proposed, in which data transformation and analysis techniques were used to obtain more detailed information about the sector. Key words: Biodiesel, export, market opportunity, demand, production costs.